Lahad Datu hero Supt Zulkifli awarded posthumous degree - Sunday, Star (Sunday Star, 2013)
SINTOK: Lahad Datu hero Asst Supt Zulkifli Mamat, who was killed in a shootout with terrorists in Kampung Tanduo, Lahad Datu,Sabah, last March, received the posthumous Bachelor of Communication (Honours) degree at the 26th convocation of Universiti Utara Malaysia (UUM) here.The degree was presented by Yang di-Pertuan Agong Sultan Abdul Halim Mu'adzam Shah, who is UUM Chancellor, to his widow Nor Aziah Noor, yesterday.